ANALISIS SISTEM KESESUAIAN DALAM MENGOPTIMALISASIKAN PELAYANAN NASABAH PADA PEMBIAYAAN DI AREA CONSUMER FINANCING STAFF BSI JAKARTA KC FATMAWATI 2 - Umdah Aulia Rohmah; Ulya Darojah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This article aims to analyze customer service in financing in the Consumer Financing Staff (CFS) area of Bank Syariah Indonesia (BSI) KC Jakarta Fatmawati 2. An effective service system is needed to optimize customer experience in accesing financing products. This study examines the factors that contribute to satisfaction in customer service, including bussines analysis, staff performance evaluations, and customer satisfaction measurement. The results of the study indicate that BSI KC Jakarta Fatmawati 2 continues to strive to improve service quality and operational efficiency, especially innthe consumer financing sector, by optimizing the role of Consumer Financing Staff (CFS). Improving the competence of CFS employees, utilizing technology, and the role of Consumer Financing Staff. Improving technology, and implementing effective strategies in satisfying customer, and strengthening of Bank Syariah Indonesia (BSI) position in the market.